Ebosin Attenuates the Inflammatory Responses Induced by TNF-α through Inhibiting NF-κB and MAPK Pathways in Rat Fibroblast-Like Synoviocytes. (17th March 2022) - Zhang, Yang; Wang, Lifei; Bai, Liping; Jiang, Rong; Wu, Jianbo; Li, Yuan
Abstract : Tumor necrosis factor- α (TNF- α ) lies at the apex of signal transduction cascades that results in induced destruction of joints in rheumatoid arthritis. It is therefore of great medicinal interest to modulate the cellular responses to TNF- α . Ebosin, a novel exopolysaccharide derived from Streptomyces sp, has been demonstrated to have remarkable therapeutic actions on collagen-induced arthritis in rats, while it also suppressed the production of IL-1 β, TNF- α, and IL-6 at both mRNA and protein levels in cultured fibroblast-like synoviocytes. In order to further understand the potential mechanisms involved in the anti-inflammatory effects of ebosin at molecular level, we investigated the impact of it on the activation of MAPK and NF- κ B pathways following TNF- α induced in fibroblast-like synoviocytes (FLS). The results showed that the phosphorylation levels of TNF- α -induced p38, JNK1, JNK2, IKK α, IKK β, and I κ B, as well as NF- κ B nuclear translocation, were reduced significantly in FLS cells in response to ebosin. Furthermore, we proved that ebosin decreased the level of NF- κ B in the nucleus and blocked the DNA-binding ability of NF- κ B using electrophoresis mobility gel shift assay. Besides, low levels of matrix metalloproteinases (MMP-1 and MMP-3) and chemokines (interleukin-8 and RANTES) were found in TNF- α -stimulated fibroblast-like synoviocytes treated with ebosin. These results indicate that ebosin can suppress a range of activities in both MAPK and NF- κ B pathways induced by TNF- α in rat fibroblast-like synoviocytes, which provides a rationale for examining the use of ebosin as a potential therapeutic candidate for rheumatic arthritis.